Comparison of two combined antiretroviral treatment regimens in the management of HIV in pregnancy: an observational study. (17th November 2021) - Tate, Danielle L.; Sublette, Nina K.; Christiansen, Mary E.; Samson, Fernand D.; Wang, Jenny Q.; Rodriguez, Marcella; Seif, Karl; Salama, Rosana; Gomez, Luis M.
Abstract: Objective: Combined antiretroviral therapy (cART) in pregnancy traditionally included two nucleoside reverse transcriptase inhibitors plus 1 protease inhibitor (PI). Recently, integrase strand transfer inhibitors (INSTI) have been approved for use in pregnancy. We sought to compare the rate of undetectable VL near delivery in pregnant HIV-infected women receiving INSTI-based versus PI-based cART. Material and methods: Prospective cohort study (January 2010–March 2017) of pregnant HIV-infected pregnancies receiving care in a single obstetric infectious disease clinic. Included pregnancies (total = 171; INSTI − group = 111, PI − group = 60) had at least 2 VL (before and after intervention) during pregnancy. The primary outcome was the rate of undetectable VL near delivery. Results: We found comparable rates of undetectable HIV VL near delivery in pregnancies treated with INSTI-cART (74/111, 66.7%) compared to PI-cART (34/60, 56.7%; [adjusted p = .116, RR 1.26, 95% CI 0.92–2.59]). Compared to the PI-group, pregnancies in the INSTI-group showed lower median HIV VL near delivery (20 versus 50 copies/mL; adjusted p = .0454) and greater VL reduction (adjusted p = .0185). There were 3/171 (1.75%) infants diagnosed with HIV, 1 in the INSTI-group and 2 in the PI-group ( p = .5635, RR 0.51, 95% CI 0.10–2.53). Conclusion: Pregnant HIV-infected women receiving either INSTI- or PI-based cART achieved comparable rates of undetectable HIV VL near delivery with similar perinatal transmission.